2003
DOI: 10.1007/s11746-003-0831-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation of FA and catfish and menhaden oils at different refining steps

Abstract: The thermal degradation (weight loss) of individual FA and of catfish and menhaden oils collected from different refining steps was investigated by thermogravimetric analysis. The heat resistance of FA was partially dependent on chain length and degree of unsaturation. The weight loss of catfish and menhaden oils increased with increased heating temperatures, regardless of the oil refining process. All oil samples (except crude catfish oil) were decomposed after the heating temperature reached 550°C. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 8 publications
1
20
1
1
Order By: Relevance
“…AND OIL IMPREGNATED PRESSBOARDS Thermogravimetry (TG) is a technique in which the mass of a substance is measured as a function of temperature whilst the substance is subjected to a controlled temperature programme [17][18][19][20][21]. It is a useful technique applied to determine the thermal stability of oils and fibers (cellulose) [18][19][20][21].…”
Section: Thermal Stability Behavior Of Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…AND OIL IMPREGNATED PRESSBOARDS Thermogravimetry (TG) is a technique in which the mass of a substance is measured as a function of temperature whilst the substance is subjected to a controlled temperature programme [17][18][19][20][21]. It is a useful technique applied to determine the thermal stability of oils and fibers (cellulose) [18][19][20][21].…”
Section: Thermal Stability Behavior Of Oilsmentioning
confidence: 99%
“…It is a useful technique applied to determine the thermal stability of oils and fibers (cellulose) [18][19][20][21]. The thermal stability behaviors of natural ester/pressboard insulation system and mineral oil/pressboard insulation system aged for different times were compared firstly in this paper.…”
Section: Thermal Stability Behavior Of Oilsmentioning
confidence: 99%
“…Entre estas últimas el comportamiento de fase y la estabilidad son aspectos importantes que determinan sus usos potenciales. Por sus ventajas en términos de precisión y sensibilidad, la calorimetría diferencial de barrido (DSC, por sus siglas en inglés) y el análisis termogravimétrico (TGA, por sus siglas en inglés) han sido utilizados recientemente para evaluar la calidad, el comportamiento térmico de fase y la estabilidad de GyA (Gouveia de Souza et al, 2004;Santos et al 2001Santos et al , 2002Sathivel et al 2003;Tan y Che-Man 2000).…”
Section: Patrón De áCidos Grasosunclassified
“…According to Dinamarca, Garrido, & Valenzuela (1990), the use of deodorization temperatures higher than 1408C probably causes a reduction in the content of EPA and DHA in the fish oil by the formation of trans fatty acid by thermal degradation. Fairly recent studies Shativel, Prinyawiwatkul, Negulescu, King, & Basnayake, 2003) have shown that degradation (loss) of PUFA occurred readily at temperatures above 1808C, cyclization of unsaturated fatty acids takes place at higher temperatures (42008C), whereas triacylglycerols polymers and dimers were found in the polar fraction of deodorized fish oil at temperatures higher than 2208C. Therefore, the quality of the refined oil is strongly dependent on the operation conditions used during refining and specially during deodorizing.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%